Model-model Pengembangan Kurikulum di Sekolah - Ramadhan, M. Rayhan; Pohan, Nelliana; Nasution, Abdul Fattah (Lembaga Yasin AlSys, 2023)
This research explores the curriculum development model in schools. This research, sometimes referred to as a type of library research, or library research, involves research or obtaining materials from various sources such as magazines, books, articles, and others that are relevant to the problem. to be solved. The output of this research is curriculum development, namely the process of curriculum planning and design by curriculum developers, and the activities carried out so that it becomes teaching materials and reference materials to achieve national education goals. In designing the curriculum, teachers can choose from several models including: Tyler model, Taba model (converter model), Wheeler model, Skillback dynamic model. Curriculum development procedures include curriculum planning, curriculum organization, personnel records, and curriculum management. Curriculum implementation is the process of putting ideas, concepts and policies into practice, so that it has an impact on changes in knowledge, skills and values. student attitude. The success of curriculum implementation depends on the availability of information about the implementation plan and the support of all resources in this implementation.